PENGARUH KINERJA BANK TERHADAP NILAI PERUSAHAAN PADA BANK UMUM YANG TERDAFTAR DI BURSA EFEK INDONESIA - Hendratni, Tyahya Whisnu (Economic Faculty, Attahiriyah Islamic University, 2019)
The purpose of the study is to examine the antecedents of corporate value on commercial banks listed on the Indonesia Stock Exchange. The financial appearance of money from financial ratios is ROA (Return on Assets) and ROE (Return on Equity). The object of this research is commercial banks listed on the Indonesian stock exchange. After the sample is taken to be observed using the purposive sampling method, there are 74 manufacturing companies. The results of this study indicate that ROA and ROE simultaneously have a significant effect on the value of the company. However, partially, only ROE has a significant effect on the value of the company and NPL. Keyword : ROA (Return on Asset), ROE (Return on Equity), Non Performing Loan (NPL)